Equilibrium of Trichloroethylene Adsorption from Aqueous Solution onto Activated Carbons - Robert Pełech (Adsorption Science & Technology)
The adsorption of trichloroethylene from aqueous solutions onto three activated carbons (DTO, AG5, WD-ekstra) was studied. Adsorption isotherms within the temperature range 298–343 K could be described by the Freundlich and Dubinin–Astakhov equations. The characteristic curves for the adsorption processes were determined. It was found out that the temperature dependence of the adsorption equilibrium was well described by the Dubinin–Astakhov model. The isosteric enthalpy of the adsorption was determined. The Do model and combinations of the van't Hoff and Dubinin–Astakhov equations in the form of a logarithmic equation were used to describe the dependence of the adsorption isosteric enthalpy on the degree of filling.